Developing Local-based English Module with Scavenger Hunts to Foster Pancasila Learners Profile - Haiyudi, Haiyudi; Tohir, Muhammad; Agil, Sofwan Arif; Safira, Tiara Putri; Budiawan, Hendra; Andini, Andini; Art-in, Sitthipon (Universitas Muhammadiyah Mataram, 2023)
Since this research was conducted, Junior high school, 1 Kepulauan Pongok has just started implementing the Kurikulum Merdeka (Independent Curriculum). Therefore, this research aims developing an English Module with local content to strengthen Pancasila Learners’ Profile. This belongs to Research and Development using 4D (defining, designing, developing, disseminating) approach. The sample was an English teacher and 31 students of class IX at Junior high school, 1 Kepulauan Pongok. The data were gained through interview and observation as the need analysis process. Distributing questionnaire is another data collecting technique to be then quantitatively analyzed using comparative analysis to the prescribed criteria. Based on the results of the validity questionnaire conducted by two expert validators, an average percentage of 86.40% was obtained as very valid. The practicality results from the students’ side show a percentage of 92.50% and 87.50% from the teachers which indicates very practical category. It can be concluded that the local cultural values of Bangka Belitung integrated to the English module with Scavenger Hunts are suitable, practical, and useful for students and teachers. Researchers further recommend the use of this module for teaching English, especially for the type of descriptive text that is appropriate to learning outcomes.